Guideline-adherence regarding critical time intervals in the German Chest Pain Unit registry - Vafaie, Mehrshad; Hochadel, Matthias; Münzel, Thomas; Hailer, Birgit; Schumacher, Burghard; Heusch, Gerd; Voigtländer, Thomas; Mudra, Harald; Haude, Michael; Barth, Sebastian; Schmitt, Claus P.; Darius, Harald; et al. (European heart journal - acute cardiovascular care, 2020)
Background:Since 2008, the German Cardiac Society certified 256 Chest Pain Units (CPUs). Little is known about adherence to recommended performance measures in patients with suspected acute coronary syndrome (ACS) presenting to CPUs. We investigated guideline-adherence regarding critical time intervals and selected performance measures in German Chest Pain Units.Methods:From 2008 to 2014, 23,804 consecutive patients with suspected ACS were prospectively enrolled in the Chest Pain Unit registry of the German Cardiac Society.Results:Median time from symptom onset to first medical contact was 2 h in patients with ST-elevation myocardial infarction (STEMI) and 4 h in patients with unstable angina and non-STEMI (NSTEMI). In patients with STEMI, median time from hospital admission to percutaneous coronary intervention (PCI) was 40 min and median time from first medical contact to PCI was 1 h 35 min. Primary PCI was performed in 94.7% of patients with STEMI, 70.0% of patients with NSTEMI and 37.4% of patients with unstable angina. PCI was performed during the first 24 h in 79.5% of patients with NSTEMI and the first 72 h in 89.0% of patients with unstable angina. Electrocardiograms were performed in 99.5% after a median of 6 min after admission and obtained within 10 min in 71%. Interestingly, 56.1% of patients were found to have non-ACS diagnoses, underlining the importance of access to additional diagnostic modalities including echocardiography, stress testing or computed tomography.Conclusions:Guideline-adherence regarding critical time intervals and primary PCI rates is good in German Chest Pain Units. More than half of patients admitted with suspected ACS had non-ACS diagnoses. Improvements in pre-hospital time delays through public awareness programmes are warranted.
Gesehen am 27.02.2020
Published online: March 15, 2018